1981
DOI: 10.1007/bf01401679
|View full text |Cite
|
Sign up to set email alerts
|

Determination of tranexamic acid (AMCA) and fibrin/fibrinogen degradation products in cerebrospinal fluid after aneurysmal subarachnoid haemorrhage

Abstract: Six patients with recently ruptured intracranial aneurysms were treated preoperatively with tranexamic acid (AMCA). Two patients received 6 g daily in i.v. infusion, two had 6 g daily by i.v. injection, and two patients were given AMCA 9 g daily by mouth during the first week after bleeding. Serial assays of AMCA and fibrin/fibrinogen degradation products (FDP) in cerebrospinal fluid (CSF) were performed during 6--13 days after the initial subarachnoid haemorrhage (SAH). Judged from the decline in CSF-FDP, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Unfortunately, while antifibrinolytic drugs reduced the risk of rebleeding, the overall management outcome was not significantly different, primarily because of a high incidence of cerebral infarction due to vasospasm. Similar results were recorded by Fodstad 14 in a randomized study of tranexamic acid. This group found that the mortality rate was higher in patients who received antifibrinolytic therapy, despite a lower rebleeding rate.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Unfortunately, while antifibrinolytic drugs reduced the risk of rebleeding, the overall management outcome was not significantly different, primarily because of a high incidence of cerebral infarction due to vasospasm. Similar results were recorded by Fodstad 14 in a randomized study of tranexamic acid. This group found that the mortality rate was higher in patients who received antifibrinolytic therapy, despite a lower rebleeding rate.…”
Section: Discussionsupporting
confidence: 88%
“…The severity of vasospasm appears to be related to the amount and duration of blood in the basal cisterns. 14 The overall management outcome in patients with aneurysmal SAH for whom delayed surgery is planned may be improved if the reduced risk of rebleeding brought about by antifibrinolytic drug administration could be combined with an agent that would prevent ischemic complications. Recent work on vasospasm has centered on the use of drugs that increase intracellular binding of calcium or that decrease calcium entry into vascular smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…- 23 Focal parenchymal damage may also increase fibrinolysis within the CSF and plasma. The perianeurysmal clot may be dissolved by this increased fibrinolytic activity.…”
mentioning
confidence: 99%
“…31 - 32 The drugs have a short half-life, ranging from 1 to 3 hours. 23 - 3334 The daily dose of EACA, which is the most commonly used drug in the United States, is 24-36 g; that of tranexamic acid, which is most popular in Europe, is around 6 g (4-12 g).…”
mentioning
confidence: 99%
“…The variable reported results of antifibrinolytic treatment may be attributable to differences in the dosage, duration, route of administra tion and in the selection of drug. The daily dose of epsilon aminocaproic acid, which is the most commonly used drug in the United States, varies between 24 and 36 g, that of tranexamic acid (TA), the more popular choice in Europe, between 4 and 12 g. Suffi cient dosing of anlifibrinolytic drugs can be surveyed by measuring the concentration of the fibrin degradation products (FDP) in the cerebrospinal fluid [7,14,17,19], whereby an increase of FDP indicates enhanced fibri nolytic activity and, hence, the risk of disso lution of the occluding perianeurysmal fibrin plug.…”
Section: Introductionmentioning
confidence: 99%